1978
DOI: 10.1038/sc.1978.46
|View full text |Cite
|
Sign up to set email alerts
|

Electro-ejaculation of a complete paraplegic followed by pregnancy

Abstract: Abstract. Mter having experimented with electro-stimulation on monkeys, the authors have put it into practice with the paraplegic. They report observations on pregnancy of a woman with a complete paraplegic below T4 who was injured IS years ago. Nineteen electro-stimulations and seven artificial inseminations were necessary. The electro stimulation is easy and can be repeated at will.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…12,[17][18][19] Many investigators have suggested that the stasis of semen in the ejaculatory ducts leads to the deterioration in sperm motility. 13,15,20,21 Brindley 21 has shown a progressive increase in sperm motility with repeated electro-ejaculation. Francos et al 20 helped to increase the motility of a man with repeated electro-ejaculations from 0 to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…12,[17][18][19] Many investigators have suggested that the stasis of semen in the ejaculatory ducts leads to the deterioration in sperm motility. 13,15,20,21 Brindley 21 has shown a progressive increase in sperm motility with repeated electro-ejaculation. Francos et al 20 helped to increase the motility of a man with repeated electro-ejaculations from 0 to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Many possible factors contributing to poor semen quality in SCI males have been identi®ed, and include seminal¯uid stasis, 45 urinary tract infection, 46 increased scrotal temperature, 47,48 antisperm antibodies, 35,49 ± 51 urine contamination due to retrograde ejaculation, 28 catheter composition, 24 the use of lubricants, 24,27 endocrine disturbances 52 and increased reactive oxygen species in semen. 53 The method of bladder management used has also been shown to a ect semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…The ®rst healthy live birth from EEJ was documented in 1978, after cervical inseminations. 17 Since then, the conception rate of SCIP following in conjunction with IUI or IVF/ICSI consists mainly of anecdotal case reports and case series. 8 ± 10,14,20,24,25 The present study, as well as other studies, demonstrates clearly the improvement in the fertility results during the last decade.…”
Section: Discussionmentioning
confidence: 99%